Cannabis-Induced Mania Following COVID-19 Self-Medication: A Wake-Up Call to Improve Community Awareness - Kaggwa, Mark Mohan; Bongomin, Felix; Najjuka, Sarah Maria; Rukundo, Godfrey Zari; Ashaba, Scholastic (International medical case reports journal, 2021)
Self-medication is becoming common during the coronavirus disease −2019 (COVID-19) pandemic due to the increasing popularity of home-based management of asymptomatic and mild cases. In this case report, we describe a patient who developed manic symptoms as a result of self-medication with a regimen containing cannabis to manage COVID-19 symptoms.A 52-year-old man with no prior history of a mental disorder, presented with a one-week history of talking more than usual, poor sleep, destructiveness, irritability, and altered mental status, following use of homemade remedies containing oranges, garlic, ginger, onions, honey, lemon, and cannabis to treat COVID-19 related symptoms over a 2-week period. This was his index presentation with such symptoms in his life. He had never used any substance of addiction before, did not have any known chronic medical condition, and had no family member with a history of any known mental illness. He was a suspect because his father had tested positive for COVID-19 and was undergoing treatment. He tested negative for COVID-19 after 3-weeks of initial COVID-19 like symptoms, urine sample was positive for tetrahydrocannabinol (THC), and he had normal investigations. He was managed with a mood stabilizer (oral carbamazepine at a dose of 200mg three times daily), antipsychotic (chlorpromazine 200mg twice daily), a sedative (diazepam 10mg at before bedtime), and occupational therapy. All manic symptoms resolved in a period of two weeks. Cannabis induced mental illness following self-medication for COVID-19 like symptoms is on the rise in the population. Due to increasing COVID-19 cases globally, hospital congestion, the popularity of home-based care guidelines for asymptomatic and mild COVID-19 to reduce hospital burden in many countries, and easy access to cannabis. With no approved cure for COVID-19, patients are turning to natural remedies to relieve symptoms of COVID-19. Emphasis on prevention of this insalubrious self-medication among the COVID-19 patients is needed to stop complication related to cannabis use.
Keywords: COVID-19, cannabis, mania, bipolar, mental disorder, self-medication, cannabis-induced mania, homemade remedies for COVID-19, cannabis use complication